Menimbang Daya Saing Pariwisata Indonesia (Dibandingkan Singapura, Malaysia, Dan Thailand) - Vonny Setianda; Roos Kities Andadari (Forum Manajemen Indonesia (FMI), 2015)
Experience from many countries shows that tourism contributes greatly to the economic growth that can improve the welfare and quality of citizens’ lives. To enhance the role of the tourism sector to improve the economy, increasing the competitiveness of this sector is the key. For Indonesia, which has great potential in the tourism sector, tourism development strategies are needed to improve the competitiveness of the tourism industry. The purpose of this study is to determine the position of competitiveness in Indonesia’s tourism sector, especially compared to some major ASEAN countries, and propose appropriate tourism development strategies. After mapping the condition of Indonesia’s tourism competitiveness compared to some other major ASEAN countries, this study uses STP (segmenting, targeting, and positioning) to find appropriate tourism development strategies. This research utilizes secondary data. The results show that compared to some other major ASEAN countries (Singapore, Malaysia and Thailand), Indonesia's tourism competitiveness in some aspects is low, although this condition has improved in recent years. However, given the demands of the dynamic tourism market, the competitiveness needs to be improved continuously. This necessitates special strategies, so that the efforts match with the target. Keywords: Indonesian tourism, competitiveness of the tourism industry, tourism development strategies